A review on diabetic foot challenges in Guyanese perspective - Kurup, Rajini; Ansari, Abdullah Adil; Singh, Jaipaul (Diabetes & metabolic syndrome clinical research & reviews, 2019)
Diabetes mellitus signifies a major public health threat worldwide. Type 2 diabetes has been reported as the fourth leading cause of death and has affected 15.5% of the adult population in Guyana, South America. Diabetes has also led to major lower extremity amputation at the only referral public hospital in Guyana. Diabetic foot and related complications are known to be multifactorial. Conclusion: In this review, we highlight the information on the diabetic foot and related complications with an emphasis on Guyanese background.